Effects of phenolic constituents of Luffa cylindrica on UVB-damaged mouse skin and on dome formation by MDCK I cells - Masahiro Umehara; Takayuki Yamamoto; Ryouichi Ito; Shiori Nonaka; Koji Yanae; Masahiko Sai (Journal of Functional Foods, 2018)
We showed that Luffa cylindrica extract prevented transepidermal water loss in UVB-irradiated hairless mice. Phenolic constituents were detected in L. cylindrica by high-performance liquid chromatography, and 12 phenylpropanoids were isolated and confirmed by NMR and negative-ion mode mass spectroscopy. 4-O-caffeoyl-glucose, 6-O-caffeoyl-glucose, 4-O-p-coumaroyl-glucose, 6-O-p-coumaroyl-glucose, 4-O-feruloyl-glucose, 6-O-feruloyl-glucose, caffeic acid, and ferulic acid were isolated from L. cylindrica for the first time. The L. cylindrica extract and phenylpropanoids were found to promote the dome formation by Madin–Darby canine kidney I epithelial cells, with p-coumaric acid being the most effective. Furthermore, p-coumaric acid upregulated the expression of aquaporin-3 (AQP3) mRNA in a dose- and time-dependent manner. These results suggested that L. cylindrica extract enhances the water permeability of the skin, owing to the AQP3 expression induced by p-coumaric acid. Therefore, L. cylindrica extract might contribute to the treatment of diseases such as dry syndrome, which cause the tissue’s inability to retain moisture.